A redefinition of the genus Troglocharinus Reitter, 1908, with description of new species (Coleoptera, Leiodidae, Cholevinae, Leptodirini) - Fresneda, Javier; Rizzo, Valeria; Comas, Jordi; Ribera, Ignacio (Zootaxa, 2021)
We redefine the genus Troglocharinus Reitter, 1908 based on a phylogenetic analysis with a combination of mitochondrial and molecular data. We recovered the current Speonomites mengeli (Jeannel, 1910) and S. mercedesi (Zariquiey, 1922) as valid, separate species within the Troglocharinus clade, not directly related to Speonomites Jeannel, 1910, a finding corroborated by a detailed study of the male and female genitalia. In consequence, we reinstate Speonomus mercedesi Zariquiey, 1922 stat. nov. as a valid species, transfer both of them to the genus Troglocharinus, T. mengeli (Jeannel, 1910) comb. nov. and T. mercedesi (Zariquiey, 1922) comb. nov., and redescribe the genus. The study of new material from the distribution area of the former S. mengeli revealed the presence of two undescribed species, T. sendrai sp. nov. and T. fadriquei sp. nov., which we describe herein. We designate the lectotype of Speonomus vinyasi Escolà, 1971 to fix its identity, as among its syntypes there are two different species. In agreement with the results of the phylogenetic analyses we establish the synonymy between the genus Speonomites and Pallaresiella Fresneda, 1998 syn. nv.